1998
DOI: 10.1016/s0014-5793(97)01608-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of thioredoxin in Fanconi anemia fibroblasts prevents the cytotoxic and DNA damaging effect of mitomycin C and diepoxybutane

Abstract: Adult T cell leukemia derived factor (ADF)/thioredoxin (Trx) is known to be an important intracellular antioxidant involved in a number of redox reactions such as ribonucleotide reductase (RNR) as well as of tyrosinase. Since RNR is a key enzyme of nucleotide metabolism and DNA synthesis, a reduced Trx level would result in reduced enzymatic activity and cause DNA damage. Furthermore, Trx is considered to be an effective regulator of redox sensitive gene expression. The role of Trx in nucleotide metabolism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Mutant cells exhibit spontaneous chromosomal breakage 38 and increased sensitivity to the development of cytogenetic anomalies on in vitro treatment with cross-linking agents 39 such as MMC 40 and DEB. 41 Additional functions for FA proteins have also been described, including modulation of cytokine-mediated signaling, [42][43][44][45][46][47][48][49][50] responsiveness to oxidative stress, [51][52][53][54][55][56][57] and chromatin remodeling. 58 Moreover, at least 2 members of the FA genes (FANCC and FANCD2) are multifunctional.…”
Section: Genetic Analysis Of a Lymphoblastoid Cell Line From The Samementioning
confidence: 99%
“…Mutant cells exhibit spontaneous chromosomal breakage 38 and increased sensitivity to the development of cytogenetic anomalies on in vitro treatment with cross-linking agents 39 such as MMC 40 and DEB. 41 Additional functions for FA proteins have also been described, including modulation of cytokine-mediated signaling, [42][43][44][45][46][47][48][49][50] responsiveness to oxidative stress, [51][52][53][54][55][56][57] and chromatin remodeling. 58 Moreover, at least 2 members of the FA genes (FANCC and FANCD2) are multifunctional.…”
Section: Genetic Analysis Of a Lymphoblastoid Cell Line From The Samementioning
confidence: 99%
“…Well-established mechanistic information has shown that MMC-associated toxicity is dependent on oxygen levels (Clarke et al 1997;Korkina et al 2000) and is removed by low-molecularweight antioxidants (Raj and Heddle 1980) and by thioredoxin (Trx) overexpression (Ruppitsch et al 1998). Recent reports demonstrate that a) MMC exposure results in an increase in oxidative DNA damage (Pagano et al 2001); b) FA cells fail to accumulate higher MMC adduct levels in DNA than control cells (Rutherford et al 1999;Will et al 1998); and c) the ratio of MMC biadducts to monoadducts (reflective of a DNA repair defect) shows no difference in FA cells compared with normal cells (Rutherford et al 1999).…”
Section: Xenobiotics Involved In Defining Fa Phenotypementioning
confidence: 99%
“…Diepoxybutane (DEB) toxicity may be indirectly associated with redox mechanisms because its epoxide structure implies susceptibility to GSH scavenging (Bartók and Láng 1980). Similar to MMC, DEB-associated toxicity correlates with oxygen levels and oxidative DNA damage (Pagano et al 2001), whereas DEB-induced cytotoxicity and DNA damage are decreased by Trx overexpression (Ruppitsch et al 1998). DEB toxicity is modulated by GSH, and in turn, DEB results in GSH depletion Spanò et al 1998;Vlachodimitropoulos et al 1997).…”
Section: Xenobiotics Involved In Defining Fa Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Trx1 interacts directly with various intracellularsignalling molecules, as well as with transcription factors including AP-1 and nuclear factor kB (7,8), thereby affecting cell growth and cell survival. A recent study showed that overexpression of Trx in Fanconi's anaemia fibroblasts prevented the cytotoxic and DNA-damaging effects of mitomycin C and diepoxybutane (9). The cytosolic isoforms of Trx (Trxh1) were shown to be responsible for sensitivity to DNAdamaging agents, including MMS, in the green alga Chlamydomonas reinhardtii (10).…”
mentioning
confidence: 99%